Advancements in acoustic properties of natural waste biocomposites: current trends, applications, and future perspectives - Murtala, Namakka; Rezaur, Rahman; Muhammad Khusairy, Bakri; Bavya Devi, Karuppasamy; M. Shahabuddin, Ahmmad; Anthonette, James; Ismail M., M. Rahman (Springer Nature, 2025)
The global shift toward Sustainable Materials has necessitated the exploration of natural waste biocomposites as eco-friendly solutions to address the contemporary environmental and industrial noise challenges. This review paper explores recent developments in the use of natural waste biocomposites, focusing on their acoustic properties and potential applications in real-world scenarios. The integration of these Sustainable Materials into biocomposites is analyzed, with a particular focus on their performance in noise reduction, sound absorption, and overall environmental impact. Challenges and opportunities in scaling these Materials for industrial applications are also discussed. Hybrid composites and nano-reinforcement improve acoustic performance, achieving sound absorption coefficients of 0.6–0.8 at mid-to-high frequencies via optimized porosity and fiber-matrix synergy. However, barriers including …